1994
DOI: 10.1017/s0022215100128555
|View full text |Cite
|
Sign up to set email alerts
|

Blast injury of the auditory system: a review of the mechanisms and pathology

Abstract: Blast injury of the auditory system is uncommon and our knowledge incomplete. This article reviews the literature to date giving an account of the interactions of blast waves with the ear, the mechanisms of injury, the pathology, the clinical features, and an outline of management principles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 20 publications
2
49
0
1
Order By: Relevance
“…Dizziness is rarely seen [1,2,6,9,10,11,14]. While dizziness was reported in only 2 of the 110 cases described by Pahor [5] and in 2 of the 20 cases described by Bruins and Cawood [9], it was a common complaint in the cases who were exposed to explosions in closed areas reported by Kerr and Byrne [6].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Dizziness is rarely seen [1,2,6,9,10,11,14]. While dizziness was reported in only 2 of the 110 cases described by Pahor [5] and in 2 of the 20 cases described by Bruins and Cawood [9], it was a common complaint in the cases who were exposed to explosions in closed areas reported by Kerr and Byrne [6].…”
Section: Discussionmentioning
confidence: 97%
“…The pressure increases in the middle ear cavity cause movement of air through the mastoid system and the eustachian tube to the nasopharynx. Thus, people who have a wide mastoid system and an open eustachian tube have a greater risk of perforation of the tympanic membrane, due to the decreased protective role of air as a cushion [10]. While Ito et al [20] in their series of 25 cases found the mean total volume of 41 temporal bone air cells to be 4.05 B 1.59 ml, Isono et al [21] reported that it was 6 ml in 43 normal temporal bones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors such as the position of the ear in relation to the explosion, the state of the ear canal, and whether the explosion occurred in a confined space can influence the severity of damage to the ear [11,13]. The most visible type of blast-induced auditory injuries occur in the physical structures of the middle and inner ear, which include tympanic membrane perforations, ossicular disruptions, and symptoms generated from insult to the vestibular components [5,12,[14][15][16][17]. Damage to auditory components of the inner ear is of primary interest because it may be permanent and cause persistent symptoms of tinnitus [18][19][20] and hearing loss [6,17,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%